2012
DOI: 10.4028/www.scientific.net/amr.585.77
|View full text |Cite
|
Sign up to set email alerts
|

FTIR and TGA Analysis in Relation with the % Crystallinity of the SiO<sub>2</sub> Obtained by Burning Rice Husk at Various Temperatures

Abstract: Rice husk ash (RHA), a waste product of the rice industry, is rich in SiO2. The large amount of SiO2 freely obtained from it provides an abundant and cheap alternative to metallurgical grade SiO2 for many industrial applications. The detailed analysis of the physical dimensions such as length, width and thickness of four varieties (HMT, Sonam, 1001 and JSR) was done. The FTIR analysis of the ash obtained by burning rice husk at different temperatures proves the formation of nano SiO2. The study of the isotherm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Regarding the calcined samples, a characteristic peak at 1620 cm –1 derived from the conjugation bond CN are observed in the bare carbon, Si/C, and Si/Ag/C samples. Particularly, the characteristic peaks at around 1100, 800, and 480 cm –1 in the Si/C and Si/Ag/C samples can be assigned to SiO 2 due to partial surface oxidation of the Si nanoparticles . The FTIR results indicate that nitrogen-doped carbon is obtained after carbonization due to the presence of the DETA curing agent.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Regarding the calcined samples, a characteristic peak at 1620 cm –1 derived from the conjugation bond CN are observed in the bare carbon, Si/C, and Si/Ag/C samples. Particularly, the characteristic peaks at around 1100, 800, and 480 cm –1 in the Si/C and Si/Ag/C samples can be assigned to SiO 2 due to partial surface oxidation of the Si nanoparticles . The FTIR results indicate that nitrogen-doped carbon is obtained after carbonization due to the presence of the DETA curing agent.…”
Section: Resultsmentioning
confidence: 90%
“…Particularly, the characteristic peaks at around 1100 cm -1 , 800 cm -1 and 480 cm -1 in the Si/C and Si/Ag/C samples can be assigned to SiO 2 due to partial surface oxidation of the Si nanoparticles. 60 The FTIR results indicate that nitrogen-doped carbon is obtained after carbonization due to the presence of the DETA curing agent. By comparing the FTIR profiles of the samples before and after calcination, it is found that the number of the peaks within the long wavelength range is significantly reduced after calcination.…”
Section: Resultsmentioning
confidence: 97%
“…The BRHA and WRHA have similar FTIR spectrum. The strong sharp peaks at 1080 and 1083 cm −1 are attributed to Si–O–Si asymmetric stretching, along with peaks at 796 and 800 cm −1 , which are due to symmetric Si–O–Si stretching and Si–O quartz [ 27 , 28 ]. The main broad peak between 1000 and 1200 cm −1 of WRHA indicates characteristics of amorphous silica [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…The observation of cristobalite and quartz alpha in BRHA indicates that BRHA should be treated at temperatures greater than 900 °C during the combustion process [22]. On the other hand, the XRD pattern of WRHA exhibited a very small peak of quartz alpha and broadening of the cristobalite peak (at 2θ = 22.5°), which indicates the nature of amorphous silica [27]. The degrees of The XRD analysis was conducted on BRHA and WRHA particles, as shown in Figure 2a,b.…”
Section: Characterization Of Brha and Wrha Particlesmentioning
confidence: 97%
“…e FTIR curve of rice husk (Figure 3(a)) shows the predominant band of the siloxane group Si-O-Si at about 1100 cm −1 . is curve also shows the broadband between 2800 cm −1 and 3700 cm −1 , which can be attributed to the OH groups and adsorbed water [18]. As seen from Figures 3(b)-3(d), these bands are also present in these samples, however, with different intensities.…”
Section: Ftir Surface Characteristics Of Alum Rice Husk Cypress and Eucalyptusmentioning
confidence: 72%